If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -9 = 2(x + 2) Reorder the terms: -9 + 2x = 2(x + 2) Reorder the terms: -9 + 2x = 2(2 + x) -9 + 2x = (2 * 2 + x * 2) -9 + 2x = (4 + 2x) Add '-2x' to each side of the equation. -9 + 2x + -2x = 4 + 2x + -2x Combine like terms: 2x + -2x = 0 -9 + 0 = 4 + 2x + -2x -9 = 4 + 2x + -2x Combine like terms: 2x + -2x = 0 -9 = 4 + 0 -9 = 4 Solving -9 = 4 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 3x+16=96 | | 2(x+4)=17 | | 123x+10= | | 5x-7=-11 | | b-6-2b= | | 24=6(-6-3) | | (Sinx-1)(sinx-5)=0 | | 20x+85y=120 | | 5x+6=2x+3-x | | 13x^2-1x+12=0 | | -4.2n-6.5=-14.06 | | 7(5x-4)=15-8x | | 13=9x-10 | | x-7-7x= | | 0.8x+4.5=0.7x+2.6 | | 2.25(3x-4)=-5x+7 | | 13x^2-1x+13=0 | | (A-5)*(2a-6)= | | 3m+3n= | | 89t^2+55t+34=0 | | r^3+10r+9=0 | | 12(3x-5)=10x-8 | | 3x^2-x+18=0 | | -x/6=9 | | -15n+12=-11-4 | | p+0.09p=196.2 | | -2-x=-12 | | a/4=13 | | 13x+25+8x-39=7 | | 15x^2-1x+18=0 | | 6=-3-2k-3k | | 6y-2=3y+4 |